Cost and Time Performance Evaluation Based on Earned Value Analysis Method - Laila Putri Rahmadani; Susanti, Junita Eka; Putri Ayu Dwiyana (Journal of Civil Engineering and Planning (JCEP), 2025)
The execution of construction projects frequently encounters a range of challenges in the field, leading to deviations between the initial project plan and actual implementation, particularly in terms of time and cost performance. Such deviations may significantly affect the overall efficiency and effectiveness in achieving the intended project objectives. Consequently, there is a critical need for an evaluation method capable of providing a comprehensive and real-time assessment of project performance. This study aims to evaluate the performance of an infrastructure development initiative, namely the ABC toll road construction project, by employing the Earned Value Analysis (EVA) method. EVA integrates three key components—cost, schedule, and work performance—offering a quantitative framework to assess both cost efficiency and schedule adherence. The performance weights used in this study are derived from both planned values and actual on-site progress to reflect the true execution status. The data utilized in the analysis include the Budget Plan (Rencana Anggaran Biaya/RAB), planned S-curve, and weekly progress reports obtained during project implementation. The findings at the 67th week of project execution indicate an Actual Cost of Work Performed (ACWP) of Rp1,231,597,458,600.00, a Budgeted Cost of Work Performed (BCWP) of Rp1,109,547,260,000.00, and a Budgeted Cost of Work Scheduled (BCWS) of Rp1,570,000,000,000.00. The Cost Performance Index (CPI) value of 0.901 indicates that the project experienced a cost overrun of 9.9% compared to the planned budget (CPI < 1 signifies cost inefficiency).